Coastal Vulnerability – Maritime Security Nexus: Insights from the Coast of Java Island - Kusumadewi, Hemalia (Coastal and Ocean Journal (COJ), 2025)
Indonesia, as an archipelagic state with one of the world’s longest coastlines, faced significant coastal vulnerabilities, such as erosion, sea-level rise, and mangrove loss, which intersected with maritime security concerns and impacted livelihoods, communities, and sustainability. This study explored the linkage between coastal vulnerability and maritime security, focusing on Java Island. Using qualitative methods and a literature review, it examined Java’s critical coastal vulnerabilities and their influence on Indonesia’s maritime security. Key issues included environmental degradation, the well-being of coastal communities, marine ecosystem health, maritime crimes, and illegal, unreported, and unregulated (IUU) fishing, analyzed within national development and coastal policy contexts. Findings revealed common ecological threats along Java’s coasts, the interconnection between coastal vulnerability and Bueger’s Maritime Security dimensions, and the need for a maritime security perspective to address sidelined vulnerabilities during non-crisis periods. This research underscored the importance of integrating coastal vulnerability into maritime security discussions to enhance resilience, preparedness, and proactive policy-making at local and national levels.